Exiting Eden: an exploration of the evolution of humanity’s conception of divine disposition and its impact on the Earth - Stevens, Charlotte (2021)
This dissertation examines how humans conceptualise their relationship with the divine vis-à-vis the created world, positing that this in turn impacts the health of the world, where health of the world is examined via ecofeminist principles. It is argued that western culture, in its progression from antiquity to the contemporary modern era, evolves from an organismic to a mechanistic framework, and this shift results in an increased conceptual distance between the creator and the created. Using ecofeminist theory, a mechanistic framework is identified as an anthropocentric one, and the negative impacts of such anthropocentrism on the health of the world are explored from the way the earth is valued, and the impact this has on ecology, to the further centric structures (such as androcentrism) that become justified through the presence of anthropocentrism, and the impact they have on our treatment of that which is ‘Other’ to us.